EPISTEMOLOGI PENDIDIKAN KARAKTER ISLAMI DI MADRASAH IBTIDAIYAH - ARI PURNOMOAJI; Abdul Wachid B.S (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2021)
The purpose of this research is to find out how the epistemology of Islamic character education in Islamic Elementery School. This research uses descriptive qualitative research methods. The data used are qualitative data. Data obtained from observation, interviews, and documentation. The data analysis technique used in this research is qualitative analysis and hermeneutics (interpretation). Islamic character education is applied through habituation activities carried out in madrasas. The teacher has a very important role in shaping the character of Islamic students. The teacher will be an example or role model for their students. Among the habituation activities in madrassas that form Islamic character include shaking hands with teachers, praying dhuha in congregation, tadarus Al Qur'an, and Tahfidz Juz Amma. This habit will form a character that is respectful of the teacher, close to Allah SWT, diligent in praying, love al quran.